A descriptive study on catchment area analysis and customer satisfaction towards big bazaar with special reference to Vadapalani Branch, Chennai - Sanjeevkumar, Virmala; Sri, Ramachandran; Kumar .U, Pavan; S., Dhanalakshmi (IJRCM, 2012)
Customers' experience ultimately determine whether or not a company stays in business.The importance of customer satisfaction was a hot business topic in the 1980s, as customer satisfaction was considered the best window into loyalty.In the late '80s, however, researchers questioned whether customer satisfaction actually impacts overall performance.They found that the link between customer satisfaction and higher profits, ROI, or share of market is dubious.The research paper is about the identification of the customer satisfaction and catchment area of BIG BAZAAR'S Business in vadapalani branch and its service.The researcher used descriptive research, and simple random sampling to identify the sample.The sample size of 111 was included in the study. Researcher sued Chi square test to test the hypothesis.